Authentic African community development practices in a diverse society: A transdisciplinary approach - van der Westhuizen, Mariche (Verbum et ecclesia, 2021)
The South African people continuously engage in social actions characterised by intolerance, pointing to frustrations and disillusionment in a post-apartheid era. A need to find creative ways to engage diverse communities to work together to participate in their own development and well-being was identified. This article is based on long-term transdisciplinary discourse and work. The aim is to explore how the disciplines of social work, theology and the arts could contribute together towards the development of communities where participation, collaboration and cooperation as key principles of authentic community development are actively implemented. Within a transdisciplinary framework, the disciplines engaged in participatory research projects that resulted in findings that informed the development of a process where people at grassroots level become aware and more tolerant of each other, begin to work together and as such become involved in their own futures. It is concluded that by encouraging participation, collaboration and cooperation in social change processes, the South African people can be empowered towards working together and becoming involved in their own futures.Intradisciplinary and/or interdisciplinary implications: The disciplines of social work, theology and the arts entered into a transdisciplinary dialogue and work over the past years. The transdisciplinary team engaged in four participatory research projects to include input from grassroots levels to inform their understanding of how the different disciplines can better contribute towards a process of authentic community development in the diverse South African society. This resulted in the process